Child Sexual Abuse in Organizational Settings: A Research Framework to Advance Policy and Practice. (September 2019) - Harris, Andrew J.; Terry, Karen J.
Recent decades have produced growing public attention to the problem of child sexual abuse (CSA) occurring within civic institutions, school settings, youth sports, religious institutions, and other youth-serving organizations. Often amid considerable media and public scrutiny, such institutions have been called upon to improve their responses to sexual abuse incidents, address underlying organizational conditions that may foster such incidents, and develop viable systems of early intervention and prevention. These system challenges, in turn, have produced growing demand for high-quality research that can refine our understanding of the correlates and dynamics of sexual abuse within institutional settings and can help identify the parameters of effective strategies and responses. This article introduces a special issue of Sexual Abuse featuring emerging scholarship focused on CSA within organizational settings and sets forth a framework for further advancing the base of knowledge in this vital area of policy and practice.